Loss of meaning as a predictor of distress in prison - Vanhooren, Siebrecht (International journal of offender therapy and comparative criminology, 2018)
Incarceration has been described as a distressing experience, marked by important losses and accompanied by deep existential crises. Some prisoners “hit rock bottom” and are confronted with the fact that their life does not make sense anymore. Surprisingly, loss of meaning among prisoners has not been studied in a quantitative way before. In this study, we explored the relationship between loss of meaning inflicted by incarceration and distress. In a sample of 365 prisoners, univariate analyses and hierarchical multiple regression analyses confirmed that a loss of meaning positively predicted distress in prison. Differences between prison regimes predicted distress, but had no influence on the loss of meaning. Unsentenced incarceration, in contrast, did not have a direct relationship to distress, but amplified the effect of loss of meaning on distress. Psychotherapy and chaplain support did not affect the relationship between loss of meaning and distress during incarceration.